Market Reaction to Quarterly Earnings' Announcements: A Stochastic Dominance Based Test of Market Efficiency - Falk, Haim; Levy, Haim (Management Science, 1989)
The use of the CAPM in empirical research is subject to some criticism. In light of this criticism the Stochastic Dominance criteria are offered as an alternative research method for the examination of market efficiency. The underlying assumptions of the two frameworks are discussed and the Stochastic Dominance technique is demonstrated via the examination of market reaction to quarterly earnings announcements during the 24 quarters commencing with October 1962. The findings are compared to those of Watts (Watts, R. The Time Series Behavior of Quarterly Earnings. Unpublished Paper, University of Newcastle, Newcastle, N.S.W. 1975, quoted in Watts [1978].) who utilized the same data base. In contrast to Watts' conclusion, our analysis suggests that the market was efficient during the entire period examined and that no significant differences in market behavior between the first and the second 12-month periods was evident. The discord may be attributed to the relative effectiveness of the two analytical tools and some differences in the research designs.